SEKSUALITAS TIGA TOKOH PEREMPUAN DALAM NOVEL SUNYI DI DADA SUMIRAH KARYA ARTIE AHMAD DAN IMPLIKASINYA PADA PEMBELAJARAN SASTRA DI SMA - Anggerenie, Nerie; Cuesdeyeni, Patrisia; Misnawati, Misnawati (FKIP, Universitas Palangka Raya, 2020)
This study aims to describe sexuality regarding various dimensions, namely (1) biological dimensions, (2) social dimensions, (3) psychological dimensions, and (4) cultural dimensions, in Sunyi, Sumirah, and Suntini characters, in Sunyi di Dada. Sumirah by Artie Ahmad, and the objectives (5) its implications for learning literature in high school. This study uses a feminist literary criticism approach and qualitative research types. Based on the results of data analysis, the four dimensions of sexuality are found in the novel Sunyi di Dada Sumirah by Artie Ahmad. Research findings: The most dominant data is the dimension of sexuality regarding the biological dimension because in the novel Sunyi di Dada Sumirah tells a lot about the sexual urges of the three characters, namely Sunyi, Sumirah, and Suntini. The results of this study have implications for literature learning in class XI high school with basic competencies (3.20). Analyzing the messages of the two fiction books (novels and poetry collection books) that are read, namely as teaching materials. The four dimensions of sexuality in the novel Sunyi di Dada Sumirah can be used as teaching materials in Indonesian language learning materials, as the material for analyzing moral messages in the novel. There are many life problems faced by Sunyi, Sumirah, and Suntini characters in living their lives, but they are people who never give up, even though their lives are not very pleasant, so from these stories students can take lessons to be better able to protect themselves in their lives. association, environment and people around, so that students are able to have principles so that they are not easily influenced by things that are not good for themselves.